2019
DOI: 10.3389/fevo.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of N2O and CO2 Following Short-Term Water and N Fertilization Events in Wheat-Based Cropping Systems

Abstract: Greenhouse gas (GHG) emissions result from short-term perturbations of agricultural systems such as precipitation and fertilization events. We hypothesized that those agricultural systems with contrasting management histories may respond differently to application events of water and N fertilizer with respect to GHG emissions. Studies with long-term management histories consisting of no-tillage (NT) and conventional tillage (CT) were coupled with high temporal resolution, automated chambers that monitored N 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
5
10
0
Order By: Relevance
“…The significant ( P < .0001) positive correlation ( r = .29) between N 2 O and CO 2 emissions observed in the current study is consistent with previous studies (Alluvione et al., 2010; Kostyanovsky, Huggins, Stockle, Morrow, & Madsen, 2019). Increased soil respiration might reduce soil oxygen availability and lead to anaerobic conditions within soil microsites, thereby favoring denitrification (Alluvione et al., 2010; Baah‐Acheamfour, Carlyle, Lim, Bork, & Chang, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The significant ( P < .0001) positive correlation ( r = .29) between N 2 O and CO 2 emissions observed in the current study is consistent with previous studies (Alluvione et al., 2010; Kostyanovsky, Huggins, Stockle, Morrow, & Madsen, 2019). Increased soil respiration might reduce soil oxygen availability and lead to anaerobic conditions within soil microsites, thereby favoring denitrification (Alluvione et al., 2010; Baah‐Acheamfour, Carlyle, Lim, Bork, & Chang, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…8). Various studies have reported increased N2O flux after rainfall (Nobre et al, 2001;Dobbie and Smith, 2003;Smith and Owens, 2010;Gelfand et al, 2015;Schwenke and Haigh, 2016;Leitner et al, 2017;Barba et al, 2019;Kostyanovsky et al, 2019) and similar increased CO2 flux after rainfall has been reported (Lee et al, 2002;Smith and Owens, 2010;Gelfand et al, 2015;Kostyanovsky et al, 2019). However, no short-term responses of CO2 and N2O fluxes, similar to our observation upon rainfall, were reported.…”
Section: Field Observationsupporting
confidence: 86%
“…In the present laboratory test, CO2 and N2O fluxes showed different temporal behaviors from those observed by Kostyanovsky et al (2019), although observed N2O flux change was similar to that observed by Leitner et al (2017). We currently speculate that the slow increase in N2O flux may reflect a slow building-up of nitrification and denitrification microorganisms after watering, although further studies, which apprehend both biological and physicochemical aspects of the soil gas formations, are necessary for better understanding.…”
Section: Laboratory Flux Measurement Testsupporting
confidence: 48%
See 2 more Smart Citations